The Correlation of Conflict and Work Environment on Productivity Which Influence Employee Performance (Study Case on PT. Syntronic Indonesia Employee) - Wibowo, Devi; Hidayat, Rahmat (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to determine the effect of conflict and work environment on the productivity of PT. Syntronic Indonesia's employee performance. The total population in this study was 89 people with the determination of the number of samples using the Slovin formula which resulted in 80 respondents. This study uses an analysis of the Structural Equation Modeling (SEM) model to determine how much influence the independent variable has on the dependent variable through the intervening variable, carried out using the Lisrel 8.8 program. The test of this research succeeded in concluding that the negative and significant effect of conflict on the performance of the employees of PT. Syntronic Indonesia. This means that the higher the conflict, the lower the employee's performance. There is a positive and significant effect of the work environment on the productivity of employee performance, meaning that the better the work environment, the higher the productivity of employee performance. For the Productivity variable, it becomes a mediator between the work environment variable and the employee performance variable. While the productivity variable is not a mediator between the conflict variable and the employee performance variable.